ROLE OF CLINICAL PHARMACIST IN EDUCATING OBESE AND OVER WEIGHT PATIENTS FOR BETTER HEALTH RELATED OUTCOMES: Pharmaceutical Science-Clinical Pharmacy - KARAMI, Dr. DORNA; Dr. MAHVASH IRAM; Dr. SHANKAR PRASAD (International Journal of Life Science and Pharma Research, 2019)
Obesity is a chronic disease in which there is excessive fat accumulation that presents a risk to public health. Health care interventions can increase awareness about obesity and its complications and it is of great concern to motivate them to change their lifestyle in order to avoid health issues. The aim of this study was to carry out educational intervention for the obese and overweight patients to improve disease outcomes. A prospective hospital based interventional study was carried out for a period of 6 months at St. Philomena’s hospital in Bangalore. Patients visiting medicine department with a body mass index (BMI) ≥ 25 kg/m2 , patients with known eating disorders and those referred to the young adult section of the obesity clinic were included in the study. A questionnaire was prepared and was introduced to the study subjects after validation. Patient information leaflets (PIL) were given to the patients to educate them about the obesity. Scores were recorded pre and post counseling to analyze for the effectiveness of counseling. A total number of 95 obese patients were enrolled in the study who belonged to young adults and adult’s age group. Majority of patients were in age between 46-50 years. Male proportions were more than females and most of the subjects were overweight. The difference between post and pre counseling score in questions concerning their lifestyle, which includes trying out strategies to lose weight, the habit of eating fruits, performing exercises and their knowledge and effort to prevent obesity in their families were found to be statistically significant. Counseling provided with the aid of patient information leaflet was beneficial in a significant change in habits and behavior of obese subjects.